2015
DOI: 10.1155/2015/910376
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Review and Meta-Analysis of the Clinical Efficacy and Adverse Effects of Zhengqing Fengtongning Combined with Methotrexate in Rheumatoid Arthritis

Abstract: Chinese medicines are gaining wider acceptance. They have been used for treating rheumatoid arthritis (RA) for thousands of years, and the need to investigate the interaction between Chinese medicines and western medicines is widely recognized. In this study, a large number of RCTs and CCTs were analyzed to systematically assess the effects and adverse events of Zhengqing Fengtongning (ZQFTN) for RA. Eleven studies that contained 956 participants (508 in the treatment group; 448 in the control group) were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…Analysis of the clinical characteristics of patients with liver injury caused by PM and preparations showed that some patients taking normal or less than the normal doses of PM, and even some patients taking the drug only once in a relatively short period of time, developed liver damage. Several patients have a familial adverse reactions to liver organ damage (Liang et al, 2014;China, 2015;Cui et al, 2016;Cheng-Sheng and Sun, 2017). This is probably due to the presence of hereditary hepatic metabolic enzyme deficiency which in turn promotes the accumulation of toxic compounds in the process of biotransformation and metabolism, leading to PM-induced liver damage.…”
Section: Immune Damage or Liver Metabolic Enzyme Genetic Polymorphismmentioning
confidence: 99%
“…Analysis of the clinical characteristics of patients with liver injury caused by PM and preparations showed that some patients taking normal or less than the normal doses of PM, and even some patients taking the drug only once in a relatively short period of time, developed liver damage. Several patients have a familial adverse reactions to liver organ damage (Liang et al, 2014;China, 2015;Cui et al, 2016;Cheng-Sheng and Sun, 2017). This is probably due to the presence of hereditary hepatic metabolic enzyme deficiency which in turn promotes the accumulation of toxic compounds in the process of biotransformation and metabolism, leading to PM-induced liver damage.…”
Section: Immune Damage or Liver Metabolic Enzyme Genetic Polymorphismmentioning
confidence: 99%
“…MTX is a widely used disease-modifying, anti-rheumatic drug [ 22 ]. GJK is a Chinese experimental herb formula [ 23 ], and ZQFTN is a monomer drug derived from the Chinese traditional herb- Caulis Sinomenii [ 24 ]. These three drugs have been used in China for RA therapy for a long time with good effectiveness.…”
Section: Data Descriptionmentioning
confidence: 99%
“…The alkaloid, sinomenine hydrochloride (7,8-didehydro-4-hydroxy-3,7-dimethoxy-17- methylmorphinane-6-one, C 19 H 23 NO 4 ), CAS number 6080-33-7, is extracted from the Chinese herbal medicinal plant, Sinomenium acutum , and has been widely used for centuries in China to treat patients with rheumatic diseases. Clinical side effects typically associated with sinomenine hydrochloride therapy include gastrointestinal symptoms, allergic responses, increased serum alanine transaminase (ALT), dizziness, and leukopenia [ 5 , 6 ]. This report is the first to describe a case of sinomenine hydrochloride-induced agranulocytosis.…”
Section: Introductionmentioning
confidence: 99%